Clonal dynamics in pediatric B‐cell precursor acute lymphoblastic leukemia with very early relapse. Issue 1 (1st October 2021) - Antić, Željko; Yu, Jiangyan; Bornhauser, Beat C.; Lelieveld, Stefan H.; van der Ham, Cedric G.; van Reijmersdal, Simon V.; Morgado, Lionel; Elitzur, Sarah; Bourquin, Jean‐Pierre; Cazzaniga, Giovanni; Eckert, Cornelia; Camós, Mireia; et al.
Abstract: Introduction: One‐quarter of the relapses in children with B‐cell precursor acute lymphoblastic leukemia (BCP‐ALL) occur very early (within 18 months, before completion of treatment), and prognosis in these patients is worse compared to cases that relapse after treatment has ended. Methods: In this study, we performed a genomic analysis of diagnosis–relapse pairs of 12 children who relapsed very early, followed by a deep‐sequencing validation of all identified mutations. In addition, we included one case with a good initial treatment response and on‐treatment relapse at the end of upfront therapy. Results: We observed a dynamic clonal evolution in all cases, with relapse almost exclusively originating from a subclone at diagnosis. We identified several driver mutations that may have influenced the outgrowth of a minor clone at diagnosis to become the major clone at relapse. For example, a minimal residual disease (MRD)‐based standard‐risk patient with ETV6‐RUNX1 ‐positive leukemia developed a relapse from a TP53 ‐mutated subclone after loss of the wildtype allele. Furthermore, two patients with TCF3‐PBX1‐ positive leukemia that developed a very early relapse carried E1099K WHSC1 mutations at diagnosis, a hotspot mutation that was recurrently encountered in other very early TCF3‐PBX1 ‐positive leukemia relapses as well. In addition to alterations in known relapse drivers, we found two cases with truncating mutations in the cohesin gene RAD21 . Conclusion: Comprehensive genomic characterization of diagnosis–relapse pairs shows that very early relapses in BCP‐ALL frequently arise from minor subclones at diagnosis. A detailed understanding of the therapeutic pressure driving these events may aid the development of improved therapies.